The andean anticancer herbal product BIRM causes destabilization of androgen receptor and induces caspase-8 mediated-apoptosis in prostate cancer - Shamaladevi, Nagarajarao (Oncotarget, 2016)
BIRM is an anticancer herbal formulation from Ecuador. Previous study established its antitumor and antimetastatic activity against prostate cancer models. The activity of BIRM against human prostate cancer (PCa) cells was investigated to uncover its mechanism of antitumor activity. In androgen receptor (AR)-expressing PCa cells BIRM was 2.5-fold (250%) more cytotoxic in presence of androgen (DHT) compared to cells grown in the absence of DHT. In AR-positive cells (LAPC-4 and LNCaP) BIRM caused a dose and time-dependent down-regulation of AR and increased apoptosis. Exposing cells to BIRM did not affect the synthesis of AR and AR promoter activity but increased degradation of AR via proteasome-pathway. BIRM caused destabilization of HSP90-AR association in LAPC-4 cells. It induced apoptosis in PCa cells by activation of caspase-8 via death receptor and FADD-mediated pathways. A synthetic inhibitor of Caspase-8 cleavage (IETD-CHO) aborted BIRM–induced apoptosis. The effect of BIRM on AKT-mediated survival pathway in both AR+ and AR- negative (PC-3 and DU145) showed decreased levels of p-AKT(ser 473) in all PCa cell lines. BIRM dosed by oral gavage in mice bearing PC-3ML tumors showed selective efficacy on tumor growth; before tumors are established but limited efficacy when treated on existing tumors. Moreover, BIRM inhibited the LNCaP tumor generated by orthotropic implantation into dorsal prostate of nude mice. Partial purification of BIRM by liquid-liquid extraction and further fractionation by HPLC showed 4-fold increased specific activity on PCa cells. These results demonstrate a mechanistic basis of anti-tumor activity of the herbal extract BIRM.